Haemolytic Disease of the Newborn - Mohammed Mejbahuddin Mia; Muhammad Shahidul Islam; Rubaiyat Farzana Hussain; Samia Hoque (KYAMC Journal, 2023)
Background: Immune-mediated haemolytic disease of the newborn refers to a specific category of haemolytic anaemia that results from transplacental passage of IgG antibodies from a pre-sensitized mother to her fetus in utero. This occurs due to blood group incompatibility between the mother and the fetus. The clinical presentation covers a wide spectrum spanning from still births and erythroblastosis fetalis as well as infants born with only mild haemolysis to those having severe anaemia snd severe indirect hyperbilirubinaemia followed by hydrops. Objective: We describe the journey of a Rh-D negative mother who endured through six pregnancies in order to have a healthy baby. Conclusion: To highlight the importance of blood grouping and Rh typing during the first antenatal visit and subsequent monitoring of antibody titers, especially in a mother who is Rh-D negative. KYAMC Journal Vol. 14, No. 01, April 2023: 54-56